Pembangunan e-shopping berdasarkan kajian TRUST dalam aplikasi perdagangan elektronik kajian kes : kedai buku Koperasi UTM Berhad - Mohamad, Nur Iliawani (2006)
A possible reason for the delayed acceptance of the Internet as a retail distribution channel may be the lack of trust consumers have in the electronic channel and in the web merchants. MoTec model (model of Trust in e-commerce) shows some elements that can affect consumers’ trust in dealing with e-commerce transactions. Based on this model, e-shopping application for Coop Book Centre UTM Berhad will be developed to prove the extent of those elements could influence the consumers’ trust in e-commerce application. Methodology used in developing the system is Phase Development Based Methodology. The analysis and design technique is based on the Object-Oriented modeling. For the implementation phase, the programming language that going to be used is Active Server Pages (ASP).